Combined iron chelator with N-acetylcysteine exerts the greatest effect on improving cardiac calcium homeostasis in iron-overloaded thalassemic mice - Natticha Sumneang (2020)
© 2019 Elsevier B.V. The morbidity and mortality in thalassemia patients are predominantly caused by iron overload cardiomyopathy (IOC). Iron-induced cardiac intracellular Ca2+ ([Ca2+]i) dysregulation is among the core pathophysiological processes in IOC-related heart failure. Although cardioprotective roles of deferiprone (DFP) and N-acetylcysteine (NAC) have been reported, their effect on cardiac [Ca2+]i transients and Ca2+-regulatory protein expression in thalassemic mice is unknown. In the present study, iron overload condition was induced in wild-type (WT) and heterozygous β-thalassemic (HT) mice by a high-iron diet. The iron-overloaded mice subsequently received a vehicle, DFP, NAC, or DFP plus NAC co-therapy. In both WT and HT iron-overloaded mice, DFP and NAC had similar efficacy in decreasing plasma non-transferrin-bound iron, decreasing cardiac iron concentration (CIC) and relieving systolic dysfunction. DFP plus NAC co-therapy, however, was better than the monotherapy in reducing CIC and restoring cardiac [Ca2+]i transient amplitude and rising rate. All regimens produced no change in cardiac Ca2+-regulatory protein expression. We provided the first evidence regarding the synergistic effect of combined iron chelator-antioxidant therapy on cardiac [Ca2+]i homeostasis in iron-overloaded thalassemic mice, with consistent improvement of cardiac contractility.